Spirit and Sonship: Colin Gunton’s Theology of Particularity and the Holy Spirit. By David A. Höhne - Yuen, Alfred H. (The journal of theological studies, 2011)
In this book David A. Höhne examines an ingredient in Colin Gunton’s diagnosis of and prescription for ‘a perceived failure on the part of traditional Western metaphysics to account adequately for the unity and diversity of the world in which we live’ (p. 3). The ingredient, Höhne argues, is Gunton’s soteriological vision of a trinitarian social ontology: ‘all of life in creation somehow echoes the being of God’ (p. 127) in the Spirit’s threefold ‘perfection of the Messiah’s particularity’ (p. 176), so that ‘everything and everyone in creation is perichoretically united and hypostatically particular’ (pp. 2–3). In its method and delivery Höhne’s argument is a constructive appraisal of the plausibility of Gunton’s vision in theology and Scripture.